Study on The Determination of Prioritized Strategy in Developing Freshwater Fish Hatchery Business in South Konawe District - Saputra, Ade; Limi, Muhammad Aswar; Fyka, Samsul Alam (Jurnal Ilmiah Membangun Desa dan Pertanian, 2020)
The purpose of this study was to determine the prioritized strategy in the efforts to develop freshwater fish hatchery business in South Konawe District. The research was purposively carried out in South Konawe District in September-December 2019. This was a case study in freshwater fish hatchery business, with the consideration that the hatchers have been engaging in this business for long time by providing freshwater fish seeds. The informants in this study were the owners of freshwater fish hatchery business in South Konawe District. The data was analyzed using Analytical Hierarchy Process (AHP) method. It aimed to determine the strategy in developing freshwater fish hatchery businesses which is appropriate and prioritized. Based on the results of the study, it was noted that the most prioritized criteria were human resources with a weight value of 0.327, while the most prioritized alternative strategy was to conduct a comparative study on similar businesses which are considered more advanced and developed with a weight value of 0.443.